Perancangan Interior Planet Futsal Center di Surabaya - Wey, Albert (Intra, 2013)
Futsal is a sport that is growing in Indonesia, including in Surabaya. But in Surabaya futsal places available only to the extent any such futsal, toilets and drinking-eating sell it. And some visitorsÂ  feel less comfortable with the condition because it can not play futsak smoothly. So for that, we need to complete the design of some of the permanent facility with a modern design that presents a comfortable atmosphere and to help the community or the players can improve Performance in the game and in the activity. In facilities also have information about futsal place so that every visitor that comes not to play, but the information that they have not known before.